Unlocking the potential of dryland underutilised crops through market linkages approaches - Gichuru, Lilian; Mbulwe, Lloyd; Lwinya, Kabosha; Binagwa, Papias Hongera (CIMMYT, 2025)
Zambia’s dryland underutilized crops, including sorghum, millets, cowpeas, groundnuts, and pigeon peas, present a transformative opportunity to enhance food security, climate resilience, and economic growth in the country’s semi-arid regions. These drought-tolerant, nutrient-rich crops are well-adapted to thrive in marginal environments where staple crops like maize struggle, yet they remain undervalued due to policy gaps, limited market access, and low awareness of their benefits. The Business-to-Business (B2B) Forum on dryland crops, held in Zambia, Lusaka on 22nd October 2025, brought together stakeholders from research institutions, government, the private sector, and farmer organizations to discuss these challenges and catalyse investment and partnerships. Drylands crops discussed in this forum are known to be inherently resilient to water scarcity, making them ideal for climate change adaptation in regions with erratic rainfall. They are also nutrient dense (protein, vitamins (A and C), minerals (iron, calcium), dietary fibre) offering a solution to malnutrition and dietary diversity. Economically, scaling up their cultivation and use could boost rural incomes, create jobs across value chains (from production to processing), and spur industrial growth. Despite these benefits, the crops face significant hurdles: low adoption of improved varieties, fragmented value chains, inadequate storage and processing infrastructure, and policy biases. To unlock the potential of these crops, the forum recommended six priority actions: (1) Strengthen Research & Development by investing in breeding, agronomic research, and value chain analysis to develop region-specific varieties; (2) Enhance Policy Support through national strategies, subsidies, and inclusion in food programs; (3) Boost Market Linkages by facilitating partnerships between farmers, processors, and buyers, and improving infrastructure; (4) Build Capacity by training farmers on climate-smart practices and business skills; (5) Raise Awareness through campaigns to promote their nutritional and environmental benefits; and (6) Mobilize Investment via public-private partnerships and donor funding. Immediate next steps include developing policy briefs to integrate these crops into Zambia’s agricultural strategies, organizing follow-up stakeholder meetings to create action plans, piloting community processing hubs, distributing improved seeds, and establishing a multi-stakeholder platform to track progress. By scaling up these “forgotten crops,” Zambia can achieve food security, improve livelihoods, and build a climate-resilient agricultural system. The forum emphasized that coordinated efforts can transform these underutilized crops into drivers of sustainable development, ensuring a more prosperous and resilient future for Zambian communities.